(untitled) (Butwal Campus Journal, 2023)
This study aims at identifying the prevalent status of the application of local skills in classroom instructions in study area in the context of government schools in Nepal and analyzes the reasons behind the available status of the application of local skills in classroom practices in study area. It also attempts to recommend some strategies for the development of local skills oriented classroom instructions for the development of practical education through functional or task-based classroom instructions. Based on qualitative method, the data have been generated through PRA, classroom observation, and semi- structured interview. The collected data have been analyzed by using thematic analysis under interpretative paradigm. The study has revealed a poor status of the application of local skills based classroom instructions in study area along with the issues of teacher development, administrative supervision, local need, examination system and also emphasizes on addressing the development of skill-oriented local curriculum for the development of task-based classroom instructions in study area and in general.